2021
DOI: 10.3390/en14061530
|View full text |Cite
|
Sign up to set email alerts
|

Chopper-Based Control Circuit for BESS Integration in Solar PV Grids

Abstract: The power delivered by photovoltaic (PV) arrays is dependent on environmental factors, and hence the availability and quality of power delivered by the PV array is low. These issues can be mitigated by integrating a battery energy storage system (BESS) with PV arrays. The integration of the BESS with PV arrays requires controller circuits to regulate power flow between the BESS, PV array, and the load. In this paper, a boost converter-based controller is proposed. The proposed controller has higher reliability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…However, in (Rajanna and Kumar, 2021), the authors proposed a novel configuration with a lower number of switches for 6/4 pole machines. The proposed converter was modified to operate on an 8/6 pole machine, and its configuration is shown in Figure 4 The proposed converter consists of only five switches, making it a costeffective converter compared to the conventional one.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…However, in (Rajanna and Kumar, 2021), the authors proposed a novel configuration with a lower number of switches for 6/4 pole machines. The proposed converter was modified to operate on an 8/6 pole machine, and its configuration is shown in Figure 4 The proposed converter consists of only five switches, making it a costeffective converter compared to the conventional one.…”
Section: Figurementioning
confidence: 99%
“…The cost and size of such a system is bound to increase The utilization of Grey Wolf Optimization (Mohanty et al, 2017) and Genetic Algorithm (Malla and N Bhende, 2014) for MPPT has been observed to improve the efficiency and accuracy of MPPT. Novel circuit topologies and machines (Manne et al, 2020;Rajanna and Kumar, 2021) have been proposed to reduce the complexity of the interface. Reduced switching converters (Kolluru and Kumar, 2021) and the integration of DC stages (Shanthi et al, 2021) have been proven to reduce overall components.…”
Section: Introductionmentioning
confidence: 99%
“…The modeling of a lithium-ion battery involves the use of an electrical equivalent circuit in order to effectively map the various dynamics of this chemistry [25]. A simple internal resistance-based model is widely used for battery voltage, current, and SoC performance [26,27]. The simple lithium-ion/LFP model [28] adopted here is illustrated in Figure 2.…”
Section: Li-ion Batterymentioning
confidence: 99%
“…internal resistance-based model is widely used for battery voltage, current, and SoC performance [26,27]. The simple lithium-ion/LFP model [28] adopted here is illustrated in Figure 2.…”
Section: Li-ion Batterymentioning
confidence: 99%
See 1 more Smart Citation